The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1159/000282675
|View full text |Cite
|
Sign up to set email alerts
|

<i>Chlamydia trachomatis</i> Infection in the Semen of Asymptomatic Infertile Men: Detection of the Antigen by in situ Hybridization

Abstract: The prevalence of Chlamydia trachomatis and other microbes was studied in 94 semen samples from asymptomatic infertile males. Simultaneously, we sought evidence for inflammation of the genital tract by determining the polymorphonuclear granulocyte (PMN)-elastase concentration in the seminal plasma. The C. trachomatis genome was detected in 8 cases using in situ hybridization. The antigen, however, was undetectable by enzyme-linked assay (Chlamydiazyme) in the same samples. Ureaplasma urealyticum was isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
2
12
0
1
Order By: Relevance
“…The next step of investigation must therefore be the reevaluation of genus-typical IgA antibodies in seminal plasma by species-specific microimmunofluorescence. In the case of a positive reevaluation of a genital-typical serology, PCR genome detection should be supplemented by the search for genomes with in situ hybridization techniques, which may give more positive results in IgA-positive seminal plasma specimens [7]. In view of the insufficient data concerning significance and relevance of seminal chlamydial antibodies and the detection of Chlamydia in semen, it is not surprising that until now no study has revealed substantial indications for an association between questionable seminal chlamydial infection and sperm quality [6,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The next step of investigation must therefore be the reevaluation of genus-typical IgA antibodies in seminal plasma by species-specific microimmunofluorescence. In the case of a positive reevaluation of a genital-typical serology, PCR genome detection should be supplemented by the search for genomes with in situ hybridization techniques, which may give more positive results in IgA-positive seminal plasma specimens [7]. In view of the insufficient data concerning significance and relevance of seminal chlamydial antibodies and the detection of Chlamydia in semen, it is not surprising that until now no study has revealed substantial indications for an association between questionable seminal chlamydial infection and sperm quality [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…Although the spread of the pathogen by retrograde ascent into the ejaculatory ducts seems to be established, only the chlamydial origin of epididymitis is accepted [1,2]. Nevertheless, there are several indications of an association with chronic prostatitis [3,4] and also with an inflammatory response in semen [3,5,7]. In addition, infections of the male genital tract appear to occur asymptomatically [6,7], although these types of infection are difficult to detect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cette equipe [56] a trouve une difference significative de I'elastase seminale Iors de la comparaison de patients avec prostatite chronique versus temoins en bonne sante. Plusieurs auteurs ont rapporte des elevations de I'elastase granulocytaire chez des hommes porteurs d'anticorps anti-chlamydia dans le sperme [106,111]. Ceci est en accord avec les resultats present6s par Weidner en 1996 : les hommes avec des IgA et/ou IgG seminales anti-chlamydia ne differaient pas significativement des hommes sans anticorps pour n'importe lequel des parametres spermatiques & I'exception des leucocytes positifs & la peroxydase (p < 0,005) [95].…”
Section: Alterations Du Plasma Seminalunclassified
“…All other diseases of the male accessory glands, especially chronic, ascending, clinically asymptomatic infection with consequences for male fertility, have to be considered hypothetical as long as there are only individual reports of questionable rigor and the causal connection between infection of the male accessory glands and/or testicles and disturbed fertility or spermatogenesis cannot be demonstrated or the pathogenic processes involved explained. Such insufficiently rigorous findings, which are mainly interpreted as clinically asymptomatic infections, have been the demonstration of Chlamydia in culture or by electron microscope in the testicles or the epididymis [9], in culture or by PCR in the ejaculate of semen donors for artificial insemination [10,11], in the ejaculate of asymptomatic infertile men by means of in situ hybridization [12] as well as the detection of Chlamydia antibodies in the serum and/or the seminal plasma [13][14][15][16]. In this regard, the employment of methods that can only detect genus-specific antibodies does not permit particularly useful conclusions to be drawn.…”
Section: Introductionmentioning
confidence: 99%